Exhibition of oil paintings and water-colour drawings of Newfoundland, and some English pictures - Toft, Alfonso (Walker's Galleries, 1920)
This is a catalogue from an exhibition of pieces by artist Alfonso Toft, held at Walker's Galleries, London, in 1920. Included in the exhibition are English landscapes and works created from Toft's expedition to Newfoundland. Toft was the guest of Lord Rothmere, who was instrumental in the creation of several paper mills in Newfoundland, and so the dominating subjects of Toft's Newfoundland pieces are the paper mills and surrounding landscapes.